Correlation between pain intensity and upper limb limitation in subjects with cuff tendinopathy - Silva, Alyssa Conte da; Padilha, Juliana Falcão; Marques, Jefferson Luiz Brum; Marques, Cláudia Mirian de Godoy (ABCS Health Sciences, 2019)
Introduction: Rotator Cuff Tendinopathy (RMR) causes pain and impairment in shoulder function, but it is not known if both in the same proportion. Objective: Verify whether pain intensity correlates with upper limb function in subjects with RMR. Methods: Cross-sectional observational study of 60 individuals with RMR. The Visual Analogue Scale (VAS) was used to assess pain and the Disabilities of the Arm, Shoulder and Hand Questionnaire (DASH) for shoulder function. For data analysis, descriptive statistics (means and standard deviation, numerical and percentage presentation) were performed and Spearman correlation was applied using a significance level of 5%. Results: The average pain by VAS was 5.02 (moderate). Mild limitation (mean score 34.43) was found in the 30 questions of the DASH questionnaire. Regarding the optional modules, in the module intended for athletes/musicians, there was no limitation of the subjects who practiced this (average score of 11.82). In the work module there was a slight limitation (average score 35.38). There was a low correlation between pain and shoulder function (rs=0.2949; p=0.0222). Conclusion: Although subjects with RMR had moderate pain, the correlation was weak between pain and shoulder function.